Economic effects of abandoned ongoing housing project in Selangor - Nur Syahirah, Noor Izhan (2018)
The research is to deal with issues regarding on economic effects on abandonment of residential properties and housing project in Selangor. The objectives of the research are to determine the causes, effects and economic effect of ongoing housing project abandonment. Furthermore, the definition of abandoned is giving up or stopping on existing project or residential project and to pull out one’s responsibilities that have been given on person in charge shoulder. This study on the causes and Selangor effect of abandoned ongoing housing project in Selangor will cover all the cases on abandoned ongoing housing project in Selangor carefully examining the causes. It will also cover the consequences of the abandoned ongoing housing project in the affected area. This result of this research is analyzed by using two methods, which are; 1) Relative Importance Index 2) Frequency Analysis. Besides that, Selangor has the highest rate of abandoned housing project compared to 14 states in Malaysia. In Selangor State, from the total amount of abandoned housing project, 82 projects, 67% have been successfully completed or completed by JPN. While 5 projects or 6% are in various stages of rehabilitation / construction and the remaining 21 projects or 27% are in the initial planning of recovery. Next, the cause’s variation, provided from the questionnaire results that have been analyze, the most critical issues are client’s financial problems which it has the highest. Besides that, among all the related causes of house project abandonment, client’s financial problems from client-related causes has the highest RII rank (RII=0.811) which suits the propose causes of this study which are financial issues. This result is gain from the questionnaire distributed to the parties involve closely to the abandoned housing project problems. This study is to identify all methods to reduce the abandonment housing project in as it will affect the economics of a country. The impact that the never-ending abandonment of residential buildings and projects would bring several effects on real properties and its values and the economy cannot be overemphasized since some of the abandoned buildings and development projects provide the basic services that should enhance the real properties developed. The results of this study will educate the general public on the causes and effect of abandonment of ongoing housing project in Selangor with a view of reducing the issues of ongoing housing project abandonment in Selangor.